Crystal structure of poly[(N, N-dimethylacetamide-κO)(μ4-5-methylisophthalato-κ5O:O, O′:O′′:O′′′)manganese(II)]. (January 2015) - Jin, L.; Zha, L.-L.; Gao, S.; Yang, S.-Y.; Huang, R.-B.
No abstract available